Maxim Online Transportation Drivers with Pieces Framework Job Satisfaction Analysis (Case Study: Bandung City) - Tambunan, Rianti Ruth Florenza; Sihotang, Jay Idoan (8ISC Abstract Proceedings, 2022)
The role of online transportation in this era is growing rapidly because it really helps facilitate everyday human work both in the social, economic, and political fields. Many companies providing online transportation services are present in Indonesia, making competition more competitive. Each company continues to improve and develop systems to satisfy and maintain customer loyalty. The level of satisfaction from the driver's perspective on Maxim online transportation is studied in this research, which includes a population and sample collection of Maxim drivers in Bandung City. Driver satisfaction can affect service performance. This study aims to analyze driver job satisfaction on the use of the Maxim application system and know the weaknesses and strengths of the Maxim application system from the drivers. To achieve this goal, the researchers used the PIECES Framework method. The PIECES framework is an analytical method in measuring the level of satisfaction with its ability to analyze the subject matter specifically for a system. Previously the data would be collected by distributing questionnaires by applying a Likert scale. Then the data would be processed using the PIECES framework on each of the variables consisting of performance, information, economics, control, efficiency, and service. As a result of this research, the faults in the application system can be recognized using the PIECES framework's six criteria, and solutions to these problems can be provided. It will also be known which variables obtained a low satisfaction score as a consideration for the company in developing the quality system. Similarly, for factors that have reached the satisfied category, the company continues to maintain and even improve so that the driver's performance improves and may be used to predict future difficulties. Keywords : PIECES Framework, Driver satisfaction, Maxim